Factors perceived to influence rural career choice of urban background family physicians: a qualitative analysis - Szafran, Olga; Myhre, Douglas; Torti, Jacqueline; Schipper, Shirley (Canadian Medical Education Journal, 2019)
Background: Urban background physicians are the main source of physician supply for rural communities across Canada. The purpose of this study was to describe factors that are perceived to influence rural career choice and practice location of urban background family medicine graduates. Methods: We conducted a qualitative, descriptive study employing telephone interviews with 9 urban background family physicians practicing in rural locations. Those who completed residency training between 2006 and 2011, were in rural practice, and had an urban upbringing were asked: when the decision for rural practice was made; factors that influenced rural career choice; and factors that influenced choice of a particular rural location. Emerging themes were identified through content analysis of interview data. Results: We identified four themes as factors perceived to influence rural career choice - variety/broad scope of rural practice, rural lifestyle, personal relationships, and positive rural experience/physician role models. We also identified factors in four areas perceived to influence the choice of a particular rural practice location - having lived in the rural community, spousal influence, personal lifestyle, and comfort with practice expectations. Conclusion: Decisions for rural career choice and rural practice location by practicing urban background family medicine graduates are based on clinical practice considerations, training experience, as well as personal and lifestyle factors.